An assessment of the effectiveness of e-filing online tax return submission system. - Nyangari, Kudzai (Midlands State University, 2020)
The study was carried out to assess the effectiveness of e-filing an online tax return submission system. The research was necessitated by the system lags that were experienced by users especially on the due dates of various tax heads which made it difficult for taxpayers to submit their returns in the comfort of their offices but rather forced them to queue at ZIMRA offices to submit their returns manually. The research therefore seeks to assess the effectiveness of e-filing in terms of ZIMRA service delivery and ways that can be adopted to improve service delivery. A descriptive research design was adopted and a qualitative approach as used since the data was non-numerous. A population of 427 registered operators in Masvingo town was used and a sample size of 220 was used for data collection, a sample of respondents was selected using the stratified sampling technique. Data was collected through a self-administered questionnaire and interview questions which were pre-tested before administration. A total of 200 questionnaires were distributed and 183 responded; 20 interviews were scheduled and 16 were conducted unavailability of time being the reasons from the respondents. Data was anlysed through content analysis since it was qualitative in nature and was presented by way of percentages, graphs and charts. Findings revealed that e-filing is an effective tool for reducing corruption, enhancing voluntary tax compliance as well as increasing service convenience. The results also revealed that e-filing is easy to use and that it paves way for time flexibility and accuracy. The study also yielded that the system is usually affected by poor connectivity or system breakdowns as well as data security threats when accessing it with google chrome. However the study concludes that to a larger extent the introduction of e-filing succeeded in improving service delivery. The study however recommends that ZIMRA should consider expansion of the server and system upgrades to ensure that quality services are provided.